A comparative genomics study of Sinorhizobium spp. strains highlighting the molecular mechanisms underlying partner specificity in rhizobia-legume symbiosis - Rezzoug, Mohamed Abdenour; Berrabah, Fathi; Rezzoug, Asma (Laghouat : Université Amar Telidji - Département de biologie, 2025)
Bacteria from the genus Sinorhizobium can form a symbiotic relationship with various leguminous plants, such as the model legume Medicago truncatula. This plant-microbe association induces the formation of specialized plant organs called root nodules, inside which the bacteria perform symbiotic nitrogen fixation (SNF). Among the methods of controlling the symbiotic process by the plant is the secretion of phenolic compounds (PCs), which acts as signaling molecules and have a potential role in modulating bacterial communities as a defense mechanism during symbiotic nodulation. This study aims to elucidate some of the molecular mechanisms involved in the selection of plant growth promoting Rhizobacteria (PGPR) by the host and factors determining symbiont specificity. Phenolic acid bioassays coupled with a comparison of the Pan-Genome of various Sinorhizobium spp. strains revealed key differences in gene features and distribution, especially in strain-specific genes found predominately within one of the symbiotic megaplasmids of S. meliloti, pSymA. Synteny analysis showed varying presence of rctB, a plasmid transfer transcription regulator. The gene was not present in two organisms, S. meliloti AK83 and S. medicae WSM419; these two strains were shown to be susceptible to the antimicrobial effect of gallic acid (GA), indicating the importance of plasmid conjugation during symbiosis. Transcriptome analysis further supported this idea. We found that genes directly involved in plasmid transfer, such as traA relaxases and Type IV Secretion System (T4SS) proteins, genes present in pSymA, were substantially up-regulated during the N2-fixation phase of root nodulation. Protein sequence comparison showed considerable dissimilarity in proteins encoded by pSymA compared to the rest of the genome. The similar localization of plasmid transfer genes and the majority of strain-specific genes indicates the importance of the megaplasmid in determining plant-microbe compatibility and N2-fixation effectiveness. This study provides insight into the molecular differences between various strains of Sinorhizobium spp. influencing their symbiotic prowess and the potential basis for the control mechanisms of plant-microbe interactions.